Evaluation of Services For Persons With Disabilities at The Office of Population and Civil Registry Services, Enrekang District - Hairia; Sakawati, Herlina; Yamin, Muh. Nur (Teras Kampus, 2024)
Every public service provider is obliged to provide fair and equitable services to all levels of society without exception to people with disabilities. The Enrekang District Population and Civil Registry Service, South Sulawesi has implemented a strategy to improve services for people with disabilities by referring to regional regulations regarding the provision of services for people with disabilities. However, these efforts still do not provide excellent service as expected. Through this research, an evaluation analysis of the implementation of services for people with disabilities in Enrekang Regency, South Sulawesi was carried out to determine the causes of poor quality services for people with disabilities. This research uses a descriptive qualitative approach. Data collection was carried out by interviews and direct observation of the facilities and services available at the Enrekang Regency Population and Civil Registry Office, which were then analyzed using the technique introduced by (Miles et al., 2018), namely Interactive Model Analysis. The research results show that services for Persons with Disabilities at the Enrekang Regency Population and Civil Registry Office, South Sulawesi need to improve Effectiveness and Adequacy indicators. Lack of facilities, such as special toilets for people with disabilities, can hamper the service process. Apart from that, the absence of translators for the deaf makes it difficult for employees to communicate which can hamper the service process. Despite these shortcomings, in general, there have been efforts to improve accessibility for people with disabilities. Services to people with disabilities are carried out quickly and precisely, and employees are responsive in responding to the needs and complaints of people with disabilities.